Parents' involvement on teen's movie consumption in the pandemic era - Indriani, Sri Seti; Mohamad Permana, Rangga Saptya; Basit, Abdul (Jurnal Studi Komunikasi, 2022)
Abstract Watching movies at home through movie applications now has become a trend in this pandemic era. Adolescents who have online learning at home are forced to entertain themselves with indoor activities; spending more time watching movies is one example. As one of the online movie platforms, Netflix has gained 204 million subscribers in January 2021, following Amazon Prime with 150 million subscribers. This situation becomes a concern where adolescents seemingly have more freedom and access to select movies without parents' awareness. Adolescents are given trust in their competence to be conscious, critical, and analyse their content despite their age. This research's objects were to acknowledge how adolescents gain access to online movies despite the television content rating system and their parents' involvement in the adolescents' selection of movies. The research was conducted using a qualitative method with a case study approach. Informants were adolescents in the range of 11-14 years old and some parents. Results showed that most adolescents gained access to movies through online applications, namely Netflix, YouTube, Telegram, and illegal websites. These adolescents gained this information from friends and the TikTok application. Regarding the parents' involvement, most adolescents claimed that their parents did not contribute to their selection of movies, seemingly ignorant, and some parents even did not know what their children watch and do in their bedrooms. However, a few of them stated that their parents contributed to their selection of movies but sometimes gave adolescents some permission to watch unsuitable movies based on the television content rating system.